Mise en marché des petits pélagiques côtiers au Sénégal : formes de valorisation et enjeux autour de la ressource - El hadj Bara Dème; Moustapha Dème (EchoGéo)
The objective of this article is to analyze the issues related to the marketing of coastal pelagics in Senegal. Available information shows that in terms of nutritional conditions and poverty alleviation, small coastal pelagics are of strategic importance in Senegal. However, the emergence of new non-food uses and the trend of pelagic exports (growing global demand) threaten national food security and the sustainability of stocks. Unlike coastal demersal fish, where exclusive contracts are concluded between fishermen, fishmongers and fish processors, for coastal pelagics market mechanisms prevail, with landed fish being sold daily to the highest bidder. Faced with more attractive external markets, the apparent availability of fish products for the Senegalese population is consequently decreasing.